PENGARUH LINGKUNGAN SEKOLAH TERHADAP PRESTASI AKADEMIK SISWA SD - Dewi Sartika Nainggolan; Asrar Aspia Manurung (STKIP Subang, 2026)
This research aims to analyze the impact of the school environment on the academic performance of elementary school students. A quantitative approach utilizing multiple linear regression was employed to evaluate the relationship between school environment factors (facilities, climate, and teacher support) and academic exam results. The research findings indicate a significant effect of the school environment on students' academic achievement. School facilities and teacher support were proven to contribute the most to academic achievement. The results of this study emphasize the importance of improving the quality of school facilities and teacher support in an effort to enhance students' academic achievement. For future research, it is recommended to explore other factors that may potentially influence academic outcomes, such as family and individual aspects